Valganciclovir is not associated with decreased EBV infection rate in pediatric kidney transplantation - Cheyssac, Elodie; Savadogo, Hamidou; Lagoutte, Nathan; Baudouin, Véronique; Charbit, Marina; Novo, Robert; Sellier-Leclerc, Anne-Laure; Fila, Marc; Decramer, Stéphane; Merieau, Elodie; Zaloszyc, Ariane; Harambat, Jérôme; et al. (Frontiers in Pediatrics, 2023)
Introduction: Primary infection or reactivation of Epstein-Barr Virus (EBV) is a significant cause of morbidity and mortality in pediatric kidney transplantation. Valganciclovir (VGC) treatment is recommended for prophylaxis of cytomegalovirus infection, but its role for the prevention of EBV infection remains controversial. Patients and methods: All pediatric kidney transplant recipients aged <18 years old were considered for inclusion in this retrospective study. EBV negative recipients with an EBV positive donor (a group at risk of primary infection) or EBV positive recipients (a group at risk of reactivation) were included. Severe infection was defined by post-transplant lymphoproliferative disorder (PTLD), symptomatic EBV infection or by asymptomatic EBV infection with a viral load >4.5 log/ml. Outcomes were compared between patients receiving VGC prophylaxis (group P+) and those not receiving VGC prophylaxis (group P-). Results: A total of 79 patients were included, 57 (72%) in the P+ group and 22 (28%) in the P- group; 25 (31%) were at risk of primary infection and 54 (69%) at risk of reactivation. During the first year post-transplant, the occurrence of severe EBV infection was not different between the P+ group (n=13, 22.8%) and the P- group (n=5, 22.7%) (p=0.99). Among patients at risk of primary infection, the rate of severe EBV infection was not different between the two groups (42.1% in P+ vs 33.3% in the P-). A higher frequency of neutropenia was found in the P+ group (66.6%) than in the P- group (33.4%) (p<0.01). Conclusion: Our observational study suggests no effect of VGC for the prevention of EBV infection in pediatric kidney transplant recipients, irrespective of their EBV status. Adverse effects revealed an increased risk of neutropenia.